Herbal Therapy Potential of Balinese Local Plants for Degenerative Diseases: A Review - Damayanti, Ida Ayu Manik (Jurnal Pijar Mipa, 2025)
Indonesia has a rich biodiversity, including numerous medicinal plants. However, their utilisation remains limited, particularly in treating degenerative diseases. This study explores the potential of local Balinese plants as herbal therapy for diabetes mellitus and hypertension through a systematic literature review. Data were collected from scientific databases such as PubMed, Google Scholar, and Science Direct, covering publications from 2018 to 2025. Out of 117 identified articles with exclusion and the same article, 13 relevant studies were selected as primary references. The analysis indicates that plant extracts from Murraya paniculata, Vitis vinifera Var. Alphonso Lavallee, Syzygium polycephalum, Antidesma bunius, Aegle marmelos, Zingiber zerumbet, Elaeocarpus grandiflora, Artocarpus altilis, Impatiens balsamina, Tagetes erecta, Vitex trifolia, and Punica granatum show potential in managing degenerative diseases. Their bioactive compounds, including flavonoids, phenolics, tannins, terpenoids, alkaloids, and saponins, act by inhibiting key enzymes, enhancing insulin sensitivity, reducing oxidative stress, and modulating lipid metabolism. These findings suggest that Balinese local plants have promising potential as natural therapies for degenerative diseases, warranting further clinical validation.